Effect of sunscreen on vitamin D. (1st November 2019) - Neale, R.E.; Khan, S.R.; Lucas, R.M.; Waterhouse, M.; Whiteman, D.C.; Olsen, C.M.
Summary: Vitamin D is essential for bone health and is produced by the skin in response to ultraviolet radiation (UVR) from sunlight. UVR is also the main cause of skin cancer, the UK's most common type of cancer. Therefore, there have been several concerns that sun protection methods such as using sunscreen can affect vitamin D production. Researchers from the QIMR Berghofer Medical Research Institute in Australia, and the Australian National University, systematically reviewed for the first time all published experimental studies, field trials, and observational studies published between 1970 and 2017, totalling 75 studies, in order to understand the effect of sunscreen use on vitamin D levels. The researchers found that while the experimental studies (using artificial light sources in a laboratory setting) support the theoretical risk that sunscreen use may affect vitamin D, the weight of evidence from field trials and observational studies (taking place in real‐life situations involving natural sunlight) suggests that the risk is low. The researchers explain that the conditions in the experimental studies did not reflect those of the real world, so the results cannot be used to inform practical recommendations for the public. The authors of this review concluded that there is little evidence that sunscreen, when used in real‐life settings, decreases vitamin D levels and in some cases sunscreen use was associated with higher vitamin D levels. Therefore, concerns about vitamin D levels should not interfere with skin cancer prevention advice. Future trails should consider high sun protection factor sunscreens which are now widely recommended. Abstract : Linked Article: Neale et al. Br J Dermatol 2019; 181 :907–915